Algorithmic Pricing Practices and Fair Competition in Online Markets: A Study of Implementation and Regulatory Challenges - Hindiana Sava Husada (International Journal on Advanced Science, Education, and Religion, 2025)
The increasing adoption of algorithmic pricing in online markets has transformed pricing strategies by enabling businesses to adjust prices dynamically based on real-time data and market conditions. While these technologies improve operational efficiency and market responsiveness, they also raise significant competition law concerns, particularly regarding the potential for tacit collusion facilitated by pricing algorithms. Despite these emerging risks, existing competition regulations do not specifically govern the use of algorithmic pricing, creating regulatory uncertainty and enforcement challenges. This study employs a qualitative socio-legal approach through literature review, interviews, and direct observation to examine the legal implications of algorithmic pricing practices in online markets. The findings reveal that although the use of pricing algorithms has become increasingly prevalent, legal awareness among stakeholders remains limited. Furthermore, current regulatory frameworks are insufficient to address the unique characteristics of algorithm-driven pricing, making effective oversight and enforcement difficult. This study contributes to the existing literature by identifying the regulatory gaps surrounding algorithmic pricing and proposing a legal framework that emphasizes algorithm-specific regulation, enhanced supervisory capacity, and transparency obligations for business actors and digital platforms. These findings provide practical recommendations for policymakers seeking to balance technological innovation with fair market competition in the digital economy.